Pemodelan Arsitektur Sistem Informasi Manajemen Aset Menggunakan Kerangka Kerja Zachman di Kantor Kelurahan Pada Eweta - Anakoda, Getrida Loba; Tetik, Yulius Nahak; Momo, Lidia Lali (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Management of assets in government or private institutions becomes an obligation that needs to be implemented well and correctly starting from planning, Submission, The purchase, use, maintenance and removal of assets.The office of kelurahan on eweta which in the process of asset inventory is still done conventionally especially in its labeling has a problem that often occurs because it cannot be distinguished between fixed assets or moving assets so it is necessary to design a system model that can later be made as a reference in the development of asset management information system. Zachman's framework with the enterprising approach of the architecture planning is a very systematic phase because it has very comprehensive coverage where in the initial stages it needs to be planned for the architecture design to match the function and needs in the eweta office..In this architectural process, it produced a modeling business that was proposed., data architecture, application architecture, and a model of conceptual information technology that needs to be applied so it can sustain information systems that will be developed based on architectural instructions that have been designed. With an enterprise architecture approach can produce architectural models that correspond to the needs in the office of deployment on the eva, therefore, in the next phase it is necessary to draw a roadmap of implementation plan so that it can be used as a guideline or form for the development of management information systems in supporting the process of asset data management.